Eksplorasi Tenun Tapestri Dengan Tema Kerusakan Alam Akibat Sampah Sebagai Karya Seni Instalasi - Hariyatik Hariyatik (Ornamen, 2022)
The creation of textile art from the use of leftover fabric (patchwork) using tapestry weaving techniques as a campaign medium to invite changes in awareness and behavior in protecting the surrounding environment due to waste, on the other hand, the installation art genre can still be explored, so textile craft works may still have a need for development even though its use is not practical, considering the value of meaning and moral messages contained in the work to invite the audience to think about environmental damage due to waste. This creation uses the method of creating craft art according to Gustami, which is divided into 3 stages in the process of creating craft works, namely, first, the exploration stage includes collecting information data (field observations/observations) and extracting theoretical foundations (sources, references and visual references). Second, namely the design stage which includes pouring out ideas from the results of the first stage in a two-dimensional visual form by considering various aspects concerning the value of craft and visualization of selected alternative sketches into a detailed form of a prototype model. Third, the end of the embodiment stage, namely making it happen at the actual size along with the final completion of the work along with the packaging system and evaluation of the results of the completed embodiment.The creation of this textile craft resulted in 6 designs of tapestry weaving works, namely as follows: (1) Raising the concept of a non-realistic landscape form with the theme of natural damage due to waste as a source of ideas for visually processing tapestry woven structures combined using patchwork. (2) 3 of the 6 alternative design developments will be realized by using a patchwork material of polyester type, as well as using an earth tone reference.